Konsep dan Sistem Pemerintahan dalam Perspektif Islam: Upaya Mewujudkan Keadilan dalam Negara Modern - Wianto, Edi Tulus; Hasibuan, Edi Saputra (AL-SULTHANIYAH, 2026)
This study examines the concept and practice of statehood in Islamic thought by exploring the historical, theological, and philosophical foundations that shape the idea of an Islamic state. The discussion covers the characteristics of an Islamic state, its system of governance, and its relevance to modern political systems, particularly within the Indonesian context based on Pancasila. The findings indicate that Islam does not prescribe a fixed form of government but emphasizes universal principles such as justice, consultation (shura), trust (amanah), and public welfare (maslahah) as the foundation of governance. These values are contextual and adaptable, allowing their implementation within modern state systems that uphold pluralism and democracy. Therefore, the ideal state in Islam is not defined by its formal structure but by the extent to which Islamic values are manifested in governance to achieve justice and societal well-being.